Analysis of The Influence of Destination Image, Service Quality, and Experience on Destination Loyalty in The Tourism Village of Kampung Tua Bakau Serip (Pokdarwis Pandang Tak Jemu) in Batam - Anggraini, Ratih; Septiana, Jennyfer; Aliandrina, Dessy (Media Wisata, 2024)
Tourist villages are popular holiday spots because of the unique culture and character of the city that accommodates tourists. Attractions such as natural attractions that showcase the diversity of plants and animals, as well as educational opportunities about the unique traditions of tourist communities can bring in more visitors. One of the tourist villages that has received recognition from the tourism world is Kampung Tua Bakau Serip Batam which is included in the top 50 in the ADWI (Indonesian Tourism Village Award) event. Over the past six years, construction of the Kampung Tua Bakau Serip Tourism Village has continued. In the research conducted by the researcher, the aim was to determine the influence of destination image, service quality, and experience on destination loyalty. This research carried out an analysis regarding how each variable has an influence, is related, and has a positive impact on each other. This research took samples from people who had visited the Kampung Tua Bakau Serip Tourism Village. One hundred and seventy people were surveyed using non-probability sampling techniques. The research results show that destination image, service quality and experience have a significant positive influence on destination loyalty. Therefore, so that the goal of destination loyalty can continue to be achieved, the Kampung Tua Bakau Serip Tourism Village needs to be maintained and preserved.